Sistem Informasi Penjualan Barang Berbasis Web pada Valentine Digital Printing Berbasis Software Development Life Cycle - Yunita Sarlina Lende; Cecilia Dai Payon Binti Gabriel; Felysitas Ema Ose Sanga (Jurnal Sistem Informasi dan Ilmu Komputer, 2025)
A good information system is a system that can run according to needs and can provide web-based service facilities. The system for selling goods still uses face-to-face directly in the purchasing process so it is time-consuming. The solution that can be provided by researchers is to design website-based sales applications so that they can be used quickly and easily. The process of making a sales information system uses the SDLC method. The benefit of the SDLC method is the availability of a platform to communicate more effectively and build a good and efficient sales information system. The results of this study, can accelerate the process of selling and buying online easily and quickly.